Reducing Antimicrobial Usage in Small-Scale Chicken Farms in Vietnam: A 3-Year Intervention Study - Phu, Doan Hoang; Cuong, Nguyen Van; Truong, Dinh Bao; Kiet, Bach Tuan; Hien, Vo Be; Thu, Ho Thi Viet; Yen, Lam Kim; Minh, Nguyen Thi Tuyet; Padungtod, Pawin; Setyawan, Erry; Thwaites, Guy; Rushton, Jonathan; et al. (Frontiers in Veterinary Science, 2021)
Indiscriminate antimicrobial use (AMU) in animal production is a driver of antimicrobial resistance globally. There is a need to define sustainable interventions to reduce AMU in small-scale production systems, which currently represent the most widespread farming systems in South East Asia and many low- and middle-income countries. We conducted a before-and-after intervention study on a random sample of small-scale chicken farms in the Mekong Delta of Vietnam from 2016 to 2019. The study included a baseline followed by an intervention phase where farmers were provided with regular veterinary advice on flock health and husbandry, as well as antimicrobial replacement products. Of 102 recruited farms (raising >100 chickens per flock cycle), thirty-five (34.2%) entered the intervention phase, whilst the rest stopped raising chickens, mainly due to suboptimal flock performance. Through the implementation of our intervention, flock AMU was reduced in 66% (hazard ratio [HR]=0.34; p=0.002) (baseline 343.4 Animal Daily Doses per 1,000 chicken-days) and mortality in 40% (HR=0.60; p=0.005) (from a weekly baseline of 1.60 per 100). Chicken bodyweight increased by 100g (p=0.002) in intervention flocks. Our findings demonstrate that the provision of veterinary advice can achieve substantial reductions in AMU in in small-scale production systems without compromising flock health and productivity.